Effect of aging on mechanical properties of 3D printed samples using stereolitography - Veronika Drechslerová; Jan Falta; Tomáš Fíla; Radim Dvo˚řák; Daniel Kytýř (Acta Polytechnica CTU Proceedings)
This paper focuses on stereolithography (an additive manufacturing technology working on the principle of curing liquid resins layer by layer using ultraviolet radiation) and the effect of aging on the mechanical properties of the material and printed samples. The aging of the material could be a problem for its subsequent use as the stability of the mechanical properties would not be maintained and unwanted deterioration of the material could occur. As part of the research, sets of samples were printed and subjected to different aging methods and subsequently subjected to quasi-static and dynamic uni-axial load tests. From the data obtained, the basic mechanical properties of the material were calculated and compared with each other. The aim of this paper was to investigate whether aging process causes significant changes in the mechanical properties of the materials used, which could have a consequential impact on their use in different industries.